(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: Acute lymphoblastic leukemia (ALL) is presented with different immunophenotypic pattern. Objective: The purpose of the study was to evaluate the immunophenotypic pattern of ALL and also, to recognize the frequency of different ALL subtypes and treatment outcome after induction remission therapy. Methodology: This prospective study was conducted in the Department of Paediatric Hematology and Oncology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from June 2017 to July 2018 for a period of one year. Newly diagnosed admitted cases of ALL aged 1 to 17.9 years were included. Immunophenotyping from aspirate marrow samples were done in a special hematology laboratory. Patients were monitored during induction remission period with physical examination and required investigations. Result: Among 87 analyzed patients, 81 patients (93.1%) were B-cell ALL and 6 patients (6.9%) were T-cell ALL. After completion of induction remission therapy 61 patients had undergone complete remission and among them B cell ALL were 56(69.1%) and T cell were 5(83.3%) (P=0.464). None of the patient had partial response or induction failure. Complication were developed in 53(60.91%) patients during induction therapy. Most common cause of death was septicemia (22/26). Death was more in patients who had total WBC count >50X109/L (p=0.017) and received regimen B (p=0.031). Conclusion: B cell ALL was more common and most of the patients had undergone complete remission after induction remission therapy. Journal of Current and Advance Medical Research, January 2021;8(1):59-64